ON THE ISSUE OF TRAINING CADETS IN UNIVERSITIES OF THE PENAL SYSTEM FOR ANTI-CORRUPTION ACTIVITIES - Nikolaev, Sergey; Godunov, Igor; Romanov, Kirill (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Service in the penal correction system refers to activities with specific corruption risks associated with empowering employees to execute criminal sentences. This requires special training and professional development, motivation, special competencies and values that can effectively combat corruption.A generalization of the results of the theory, methodology and practice of preparing for anti-corruption activities made it possible to identify and justify the principles of training cadets at higher educational institutions of the UIS for anti-corruption activities. The methodological basis for the development of a theoretical justification for preparing cadets for anti-corruption activities was the humanistic, systemic, axiological and activity approaches. The preparation of cadets of UIS universities for anti-corruption activities requires the formation of a system of values and value orientations that determine their informed choice of anti-corruption behavior and make official activities resistant to external factors and influences. The effectiveness of preparing cadets for anti-corruption activities is achieved by the consistency of the formed value orientations, the emerging needs for their satisfaction and the integrity of law-abiding behavior. The content of training cadets should be consistent and aimed at developing qualities that will allow them to effectively perform their duties in conditions of increased corruption risks.